Persepsi Siswa Terhadap Metode Mengajar Guru Pendidikan Agama Islam di SMP Muhammadiyah 57 Medan - Aidil Azhar Faizal Lubis; Benny Fernanda; Indah Permata Sari; Hasrian Rudi Setiawan (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Teaching methods are the way teachers deliver learning material in every face-to-face meeting with students. Creative, professional teachers are required to develop approaches and choose effective teaching methods to create a conducive and enjoyable learning climate. To avoid boredom in learning, teachers can choose a method that suits the subject or sub-subject at the same time and place at once, because there are strengths and weaknesses in each teaching method. Teaching methods that are suitable for certain subjects are characterized by high student learning achievement in each learning evaluation implementation. Another factor that influences learning outcomes is achievement motivation. In the learning process, achievement motivation is very important to give to students. This is intended to stimulate students' creativity and willingness to participate in learning activities. Achievement motivation is the desire to complete something to achieve a standard of success, and to make an effort to achieve success